2017
DOI: 10.1177/1355819617714816
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of Memory Assessment Services for the diagnosis and early support of patients with dementia in England

Abstract: BackgroundPolicy makers in England advocate referral of patients with suspected dementia to Memory Assessment Services (MAS) but it is unclear how any improvement in patients' health-related quality of life (HRQL) compares with the associated costs. AimsTo evaluate the cost-effectiveness of MAS for the diagnosis and follow-up care of patients with suspected dementia. MethodWe analysed observational data from 1318 patients referred to 69 MAS, and their lay carers (n=944), who completed resource use and HRQL que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 24 publications
(57 reference statements)
0
12
0
Order By: Relevance
“…Our short‐term cost‐effectiveness analysis reported that patients attending MAS had a QALY gain according to DEMQOL‐U of 0.021 and EQ‐5D‐3 L of 0.023 over the first 6 months after referral. This study shows that the improvement in HRQL is maintained to 2 years, although the EQ‐5D‐3 L gain is smaller (0.014) than at 6 months (0.023).…”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…Our short‐term cost‐effectiveness analysis reported that patients attending MAS had a QALY gain according to DEMQOL‐U of 0.021 and EQ‐5D‐3 L of 0.023 over the first 6 months after referral. This study shows that the improvement in HRQL is maintained to 2 years, although the EQ‐5D‐3 L gain is smaller (0.014) than at 6 months (0.023).…”
Section: Discussionmentioning
confidence: 86%
“…Thirdly, this economic evaluation is based on rigourous collection of data on different measures of effectiveness (both disease‐specific and generic HQRL measures), and costs to the NHS, social care, carers, and patients (societal perspective). Fourthly, our cost‐effectiveness findings are based on longitudinal measurements of both costs and outcomes over 2 years, and hence, captures the impact of MAS over a longer period than previous studies based on a single time point and short follow up: either 3 months, 6 months, or 1 year …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations